The Role of Education in Implementing Social Justice: The Case of Shia Muslims (American Journal of Islam and Society, 2014)
In honor of World Day of Social Justice, on February 24, 2014, Shia RightsWatch and American University held the first-ever conference devoted to presentingnew paradigms for exploring how the rights of the minority Shia Muslimcommunity can be protected against such entrenched realities assubordination, injustice, violence, discrimination, and marginalization. Socialscientists define minority as a culturally, ethnically, religiously, or racially distinctgroup that coexists with, but is subordinate to, a more dominant group.This subordinancy, the chief defining characteristic of any minority, has nothingto do with numbers, a fact perhaps most vividly illustrated by South Africaunder apartheid (c. 1950-91).The conference, held at American University, was cosponsored by theMohammed Said Farsi Chair of Islamic Peace. Well-known and high caliberpolicymakers, professors, and researchers shared their findings in order tooffer solutions designed to foster peace, tolerance, and religious freedom forthis group and the regions in which they reside.In his capacity as the first occupant of the endowed Mohammed SaidFarsi Chair of Islamic Peace as well as the founder of the university-wideCenter for Global Peace, Abdul Aziz Said (School of International Service,American University) welcomed everyone. He remarked that peace is farmore than the absence of war, that it is, in fact, inclusive of social justice, ecologicalsustainability, sustainable economics, and cultural diversity (peace asthe absence of structural violence). Thus, conflict resolution is one of the buildingblocks of peace. Given that the ends we seek and the means that we employin the study of peace and conflict resolution are interconnected, teachingthese two fields must be based on a pedagogy that is itself peace and notmerely a process of certification. He argued that education about peace andconflict resolution and education for peace and conflict resolution are twosides of the same coin. Peace and conflict resolution education combine informationwith liberation and procedure with transformation. He concluded ...